Percutaneous Embolization for Ruptured Ectopic Bronchial Artery Aneurysm: A Case Report - Shi, Yaoping (Medicine (Baltimore), 2015)
Bronchial artery aneurysm (BAA) is an uncommon disease, and spontaneous rupture of an ectopic BAA can be difficult for diagnosis and life-threatening. This case study describes a 52-year-old man who presented with acute onset of right chest pain, mild tachycardia, and hypertension. The initial diagnosis of acute myocardial infarction was made, and the patient was given nitroglycerin prior to admission to our hospital. However, the patient's symptoms deteriorated. An enhanced computed tomography scan revealed a ruptured 25-mm diameter mediastinal aneurysm under the tracheal bifurcation when he was admitted to our hospital. Bronchial arteriography further demonstrated a ruptured mediastinal BAA of a bronchial artery originated from the left subclavian artery, supplying the right lobe. Transcatheter artery embolization with polyvinyl alcohol particles and microcoils was performed successfully. The patient's symptoms were gradually relieved, and without recurrence on 1 year follow-up. This case highlights the rare variation of mediastinal BAA and the role of interventional radiology in diagnosing and treating this critical condition.